Global patterns and determinants of erosion-induced soil carbon translocation - Fangli Wei; Lanhui Wang; Lizhi Jia; Yuanyuan Huang (Geography and Sustainability, 2025)
Soil erosion is a critical process influencing the global carbon cycle. However, erosion-induced carbon changes remain inadequately understood, particularly for soil inorganic carbon (SIC). There is also limited knowledge about the factors influencing soil carbon dynamics during erosion processes. Here we quantify the global translocation of soil organic carbon (SOC) and SIC due to soil erosion using data-driven global soil carbon estimates combined with a soil erosion map derived from the Revised Universal Soil Loss Equation (RUSLE) model. Our analysis reveals that global SIC and SOC translocations from soil erosion are 107.1 Tg C yr−1 and 898.4 Tg C yr−1, respectively. These translocations exhibit distinct patterns across aridity gradients and different biomes and soil types, with SIC translocation increasing while SOC translocation decreasing with aridity. Croplands exhibit significantly higher soil carbon translocation compared to natural vegetation, with SIC translocation being 2.41 times higher and SOC translocation 0.65 times higher than in forests. Topographic features (slope length and steepness) predominantly determine soil carbon translocation during erosion, with steeper and longer slopes exacerbating erosion and subsequent SIC/SOC translocation. Land use change, particularly agricultural practices, is also a critical driver. Our findings provide valuable insights into the factors influencing SIC and SOC translocation, enhancing our understanding of the global patterns and determinants of erosion-induced soil carbon dynamics.